Action games used by teachers to encourage students to improve the english languague acquisition in the teaching learning process. - Valverde Escobar, Leonardo Javier (Machala : Universidad Técnica de Machala., 2015)
El presente trabajo de investigación se centra en aclarar los principales aspectos que conlleva el uso de juegos de acción en las clases de lengua extranjera, especialmente en Inglés, mientras que utilizando los juegos se convierten en una metodología útil en el campo de la educación, juegos desempeñan un papel importante y aspectos relevantes como forma de motivación para aprender y estudiantes se sienten más cómodos en el momento de participar en clases.
The present investigation work focuses in clarify the main aspects that entails the use of action games into the foreign language classes especially in English, whereas using games become a useful methodology in educational field, games perform an important role and relevant aspects as motivational way to learn and students feel more comfortable at the moment to participate in classes.
Keywords: GAME; TEACHER; TEACHING-LEARNING; STUDENT